Effects of crises and neoliberalism on Spanish social workers: coping with meaningfulness, dissatisfaction, and withdrawal - Xoán M Lombardero Posada; Aguiar Fernández, Francisco X; Evelia Murcia Álvarez; Méndez Fernández, Ana B; Antonio González Fernández (European journal of social work, 2022)
This study aimed to examine some components of job satisfaction, work meaningfulness, and job dissatisfaction in social workers from governmental (GO), private (PO), and third sector (TSO) organisations. The study analysed the responses provided by 35 Spanish social workers concerning various work components that generate satisfaction, meaningfulness or dissatisfaction in them. The thematic analysis of their comments, grouped into job demands, job resources, and job crafting, revealed components that produce satisfaction and meaningfulness (the profession itself and coworkers’ support) and others that provoke dissatisfaction (overload, working conditions, and salaries). Similarities among the three organisations were found in the causes of satisfaction and meaningfulness. Differences were found concerning dissatisfaction: PO and TSO participants consider themselves precarious workers in terms of their overload, working conditions, and salaries; compared to them, GO social workers are considered privileged in these three components, so all participants want to work in a GO. These circumstances have been aggravated by the neoliberal policies implemented to confront the successive crises. Social workers carry out multiple coping strategies, including practices of resistance, to encourage satisfaction and meaningfulness, minimise dissatisfaction, and avoid or postpone withdrawal.